A study of natural lightweight aggregates for structural concrete - Onate, Cesar E.
This is a study of Natural Lightweight Aggregates for Structural Concrete. The natural lightweight aggregates used were pumice, cinder, and scoria which are available in the country. These were gathered from Pampanga, Laguna, and Batangas, respectively. The chemical ang physical properties of these three types of lightweight aggregates were verified first with the requirements of ASTM C330 (5) before they were employed in the concrete mixes designed. (ACI-211.2-81.2). To determine the effects of replacing lightweight fines by normal sand, three amounts of sand replacements, 0,50, and 100 percent by volume, were introduced at each compressive strength level. In the determination of plastic lightweight concrete properties, slump, air content and yield were measured. Further, compressive strength, unit weight, splitting tensile strength, shrinkage and popout tests were conducted to obtain the properties of hardened lightweight concrete. The findings showed that pumice is suitable for structural concrete. With regards to the effect of replacing lightweight fines by normal sand, structural properties of lightweight concrete were improved as the amount of natural sand was increased.